The animated video as a tool for political socialization on the intelligence services (Communication & Society, 2018)
In secrecy for decades, the terrorist attacks of in 2001 in the heart of our cities have brought the intelligence services and their role in the fight against terrorism closer to a large sector of the population. Post 9/11 studies have shown how knowledge helps to mitigate stress. In this project, the process of preparing two animated videos is described. They offer material to parents and educators that will help to inform young people that, alongside the police and the military, there is another democratic institution with people in charge of protecting them. The field work was conducted with 455 students of between 8 and 16 years old from various Spanish cities. In all, 83% of students considered that the story was of interest as well as the way it was communicated. In conclusion, the animated videos were seen by the schoolchildren as an appropriate means of communicating the role of security institutions.